Dissolution of silicate minerals and nutrient availability for corn grown successively - Krahl, Luise Lottici; Valadares, Leonardo Fonseca; Sousa-Silva, José Carlos; Marchi, Giuliano; Martins, Éder de Souza (Pesquisa Agropecuaria Brasileira, 2022)
The objective of this work was to evaluate the nutrient availability for corn (Zea mays) grown successively in pure and ground biotite schist and biotite syenite rock samples. The rock powders were subjected to chemical, physical, and mineralogical characterization, and the availability of the elements released to the plants was determined. Plant and rock materials were evaluated at the end of seven successive growth cycles. Biotite schist and biotite syenite provided nutrients – as K, Ca, Mg, Fe, and Mn – to the corn plants. The nutrients accumulated in plant tissues came mostly from minerals containing oxidizable Fe and Mn in their structure, such as biotite, chlorite, and clinopyroxene. The congruent dissolution of some of the fine particles of these minerals, solubilize elements, which may, then, be available to the plants.
Keywords: agromineral; biotite; bioweathering; congruent dissolution; nutrient availability